Extracellular polymeric substances (EPS) modulate adsorption isotherms between biochar and 2, 2′, 4, 4′-tetrabromodiphenyl ether. (January 2019) - Liu, Guangxia; Sheng, Hongjie; Fu, Yuhao; Song, Yang; Redmile-Gordon, Marc; Qiao, Yan; Gu, Chenggang; Xiang, Leilei; Wang, Fang
Abstract: Extracellular polymeric substances (EPS), chars and persistent organic pollutants (POPs) frequently coexist in the environment. However, a knowledge gap exists regarding their interactions. Therefore, we applied 2, 2′, 4, 4′-tetrabromodiphenyl ether (BDE-47) as a model POP to investigate the influence of bovine serum albumin (BSA) and sodium alginate (SA) - representing protein and polysaccharide components of EPS - on POP adsorption to biochars. Surface activities of tested biochars were characterised using nuclear magnetic resonance, X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. The adsorption capacities of BDE-47 on biochars were significantly improved by both EPS analogues: BSA at concentrations of only 5 mg L −1 and SA at 80 mg L −1 at c e = 1 S w BDE-47 concentration. However, 80 mg L −1 BSA decreased the BDE-47 adsorption capacities on biochars at the tested BDE-47 concentrations. Chemisorption and pore filling mechanisms appeared to dominate the adsorption process of BDE-47 on maize straw and wheat straw biochars. After adding BSA (or SA), a hydrophobic partition effect was found to best explain the adsorption process and linearity of adsorption was enhanced. These results progress our understanding of bioavailability and migration of POPs: especially relevant to the water industry and biochar/EPS facilitated removal of these contaminants. Graphical abstract: Image 1 Highlights: Bovine serum albumin (BSA) at 5 mg L −1 increased BDE-47 ( c e = 1 S w ) adsorption. Sodium alginate (SA-80 mg L −1 ) had a positive effect on BDE-47 ( c e = 1 S w ) sorption. BSA at 80 mg L −1 decreased the adsorption capacities of BDE-47 on biochars. BDE-47 adsorption on biochar was dominated by surface adsorption. Hydrophobic partition dominated the adsorption with the existence of BSA (or SA).